Stratigraphic and Petrographic investigations into the Permian-Triassic continental sequences of Nurra (NW Sardinia) - Gaggero, L.; Cassinis, G.; Cortesogno, L.; Ronchi, A.; Valloni, R. (Cuadernos de Geología Ibérica, 1996)
Sin resumen